Pengaruh Fatherless terhadap Kemandirian Emosional pada Remaja Akhir Perempuan Generasi Z: The Influence of Fatherlessness on Emotional Independence in Late Adolescent Generation Z Girls - Intan Khoirun Nisa; Asih Kuswardinah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The phenomenon of the diminishing psychological role of fathers in childcare is increasingly common in Indonesia, influenced in part by the strong view that fathers only serve as breadwinners. This lack of involvement has the potential to negatively impact an individual's emotional stability, particularly for women transitioning into adulthood, where they are increasingly expected to be emotionally independent and no longer dependent on their parents. This study aims to analyze the influence of this condition on the level of emotional independence in Generation Z women. The approach used was quantitative with a correlational design. Data collection was conducted online through a purposive sampling technique with 173 respondents, with the criteria of women aged 18 to 25 years in the early adult phase. The research instrument used an adapted questionnaire that had undergone feasibility testing, with the results of 44 statements being declared valid and having a fairly good level of reliability (Cronbach's Alpha of 0.670). Data were analyzed using descriptive statistics and simple linear regression. The results showed that the level of fatherlessness among respondents was in the fairly high category, with an average value of 61.37. Hypothesis testing revealed a significant correlation between these conditions and emotional independence (a significance value of 0.000 and a regression coefficient of -0.226). This finding suggests that any increase in the sense of role loss will decrease an individual's ability to manage their feelings independently. This study concludes that paternal involvement is essential as a foundation for strong family bonds. The absence of this role has been shown to hinder adolescents' individuation process significantly.